Avaliação do volume intracraniano pré e pós-operatório de crianças com craniossinostose não sindrômica usando técnica volumética de impressão 3D técnica - Sampaio, Gustavo Botelho (2024)
Background: Corrective surgery for craniosynostosis presents several challenges to students during their training, with obtaining practical experience being one of the main obstacles. The skull is a very complex bone structure located at the cephalic end of the body. The neurocranium is formed by the bony structures that surround the brain, thus ensuring its protection. During the first years of life, the baby's skull grows exponentially. Understanding the normal growth and development of the cranial shape is essential for monitoring cranial development, detecting abnormalities, and evaluating the long-term results of craniosynostosis surgery. Objective: To evaluate the intracranial volume of patients with non-syndromic craniosynostosis before and after surgical treatment using preoperative 3D printing and programming. Patients and Methods: 36 patients who underwent craniosynostosis surgery at the Hospital da Criança e Maternidade from 2019 to 2022 were selected. Ten patients were excluded because they did not meet the prerequisites. Preoperative, immediate, and late postoperative (3 months) tomography examination was performed. Reconstructing the exams using the Blender program with cranial volume calculation. 3D printing of skulls using Sethi 3D printer. Evaluation of results using Student's t-test with independent samples. Results: The study involved 26 patients, with ten presenting scaphocephaly treated with Renier's "H" cranial remodeling, five with trigonocephaly, five with plagiocephaly, and two with brachycephaly treated with fronto-orbital advancement (FOA). Cranial volumes were measured before and after surgery. For patients undergoing Renier's "H" treatment, there was an average increase of 224 cm³ between the late postoperative and preoperative stages, with smaller differences between the immediate postoperative and preoperative stages. For those treated with FOA, the average difference between late postoperative and preoperative stages was 138.8 cm³, while between immediate postoperative and preoperative stages was 129.7 cm³. Conclusion: The use of 3D shape and volumetric measurements shows that brain growth is not normal in patients with single suture craniosynostosis. Although the understanding of what causes craniosynostosis is still evolving, it seems clear after 3D shape and volume analysis that surgical correction for craniosynostosis improves brain differences between patients with craniosynostosis and healthy controls. The cranial volume gained by patients undergoing Renier's h technique and Fronto-orbital advancement is significant, showing that it may be possible to use less invasive techniques to take advantage of patients' natural volumetric gain.